2019
DOI: 10.1002/rnc.4854
|View full text |Cite
|
Sign up to set email alerts
|

Tracking and load sway reduction for double‐pendulum rotary cranes using adaptive nonlinear control approach

Abstract: Summary Because of the existence of rotational boom motion, the load sway characteristics is more complex. In particular, when the sway presents double‐pendulum phenomenon, the design of the controller is more challenging. Furthermore, the uncertain parameters and external disturbances in crane system make it difficult for traditional control methods to obtain satisfactory control performance. Hence, this paper presents an adaptive nonlinear controller based on the dynamic model of double‐pendulum rotary crane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 57 publications
(157 reference statements)
0
20
0
Order By: Relevance
“…In this section, the dynamic analysis of the rotary crane with double-pendulum effect is carried out in the light of the structure diagram shown in Figure 1 first and, then, combined with the expression of Lagrange’s kinematics equations. Finally, the following dynamic model of this type of crane system will be obtained 2…”
Section: Problem Statement and Model Transformationmentioning
confidence: 99%
“…In this section, the dynamic analysis of the rotary crane with double-pendulum effect is carried out in the light of the structure diagram shown in Figure 1 first and, then, combined with the expression of Lagrange’s kinematics equations. Finally, the following dynamic model of this type of crane system will be obtained 2…”
Section: Problem Statement and Model Transformationmentioning
confidence: 99%
“…In the past few decades, in order to achieve the dual goals of trolley positioning and load elimination, more and more scholars are devoted to this subject and a series of anti‐sway positioning control methods have been come up with. For instance, input shaping method, 2‐7 model predictive control, 8‐10 trajectory planning method, 11‐13 robust control, 14‐16 adaptive control, 17‐19 and so on. However, most control methods are proposed for two‐dimensional overhead cranes systems and 3D overhead cranes with single pendulum effect.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the supertwisting sliding mode formation maneuvers, it is possible to avoid the overestimate problem of the gain by the disturbance observer technique. So far, it is reported that the disturbance observer technique has been successfully applied to mechatronics systems, [28][29][30][31] chemical and process systems, 32 biological systems, 33 aerospace systems, 34 and so on. This paper adopts the technique for the super-twisting sliding mode formation maneuvers of uncertain multi-robot systems.…”
Section: Introductionmentioning
confidence: 99%